Study of Procurement of Temporary Waste Shelter Building in the Green Campus Program of Ibn Khaldun University, Bogor - Lutfi, Muhamad; Chayati, Nurul; Salam, Edi Nur; Insan, Muhammad Khaerul; Shulyana, Halyatunisa Dewi (Universitas Ibn Khaldun Bogor, 2025)
Waste is one of the factors of environmental damage, especially in campus areas that have a lot of waste generation. Waste is also one of the factors of environmental damage in campus areas because of lecture activities that trigger a lot of waste generation. Green Metric Universitas Indonesia is a green campus program to provide information regarding the conditions and policies of each university in the world in an effort to stop global climate change through one of the waste processing methods. The purpose of the study is to create the Ibn Khaldun University Bogor Campus as a green campus in Bogor City with supporting factors in the provision of a Temporary Shelter (TPS) for Ibn Khaldun University Bogor based on SNI 19-3964-1994, SNI 2847-2019 and SNI 1727-2020. The method used is collecting primary data on land measurements, collecting waste generation data, data on the number of academics at Ibn Khaldun University Bogor and the results of interviews with the Bogor City Environmental Service to then conduct a structural analysis of the planned building using the ETABS V21.0.0 and SPColumn applications based on SNI 2847-2019 (Structural Concrete Requirements for Buildings). The results of the structural analysis of the planned dimensions of the Temporary Shelter (TPS) of Ibn Khaldun University Bogor are planned with a size of 17.5 meters x 6 meters using reinforced concrete material and with a roof covering structure using a concrete roof structure. The specifications of the TPS UIKA Bogor structural material use a concrete quality of 24.9 MPa, a yield strength of 400 MPa (threaded) and 300 MPa (plain) steel reinforcement. The column dimensions are K30x30 cm (bearing area with main reinforcement 4D14, shear reinforcement ø10-150 mm). The dimensions of the main beam are B20x40 cm (bearing area with 2D14 reinforcement, ø10-50 mm shear reinforcement and bearing area with 2D14 reinforcement, ø10-100 mm shear reinforcement). The dimensions of the child beam are B15x25 cm (bearing area with 2D14 reinforcement, ø10-200 mm shear reinforcement). The thickness of the concrete roof slab is 12 cm (two-layer and two-way reinforcement with ø12-100 mm. The output results of the structural analysis of the planned building are purple on the columns with a strength ratio of 0.90 to 0.95 and green on the beams with a ratio of 0.50 to 0.70 which indicates that the structure is safe enough for the working load. The planned budget for the TPS UIKA Bogor building is Rp 262,459,889.